Assessment of the Techno-Economic Feasibility of Semicontinuous Production of Metarhizium anisopliae Spores - Ferreira, Daiane Bortolote [UNESP]; Mendes, Fabrício Bruno; Thoméo, João Cláudio [UNESP] (American Chemical Society (ACS), 2023)
The significant increase and indiscriminate use of chemical pesticides have led to the development of several environmental problems and adverse effects on human health. Alternatively, bioinsecticides have been successfully used for a variety of crops to control several insect infestations with efficiency and competitive costs. Metarhizium anisopliae have widely been used in sugar cane crops in Brazil, and their use is the most successful enthomopathogen program worldwide. However, the production of this propagule is semiartisanal and presents several technical bottlenecks. In order to intensify this production, all the steps of the process have been revised and more efficient techniques and procedures have been adopted to avoid exogenous contamination and increase the productivity. The most relevant modification in this semicontinuous process is the cultivation of rice in packed-bed solid-state cultivation bioreactors and the extraction of spores in rotating drums, with retention of the spores in cyclones. The economic analysis showed that this process is competitive when compared with the traditional process of spore production and with similar biotechnological processes.